Mammalian‐Cell‐Driven Polymerisation of Pyrrole. (13th March 2019) - Sherman, Harry G.; Hicks, Jacqueline M.; Jain, Akhil; Titman, Jeremy J.; Alexander, Cameron; Stolnik, Snow; Rawson, Frankie J.
Abstract: A model cancer cell line was used to initiate polymerisation of pyrrole to form the conducting material polypyrrole. The polymerisation was shown to occur through the action of cytosolic exudates rather than that of the membrane redox sites that normally control the oxidation state of iron as ferricyanide or ferrocyanide. The data demonstrate for the first time that mammalian cells can be used to initiate synthesis of conducting polymers and suggest a possible route to detection of cell damage and/or transcellular processes through in situ and amplifiable signal generation. Abstract : The rules of conducting : Mammalian cell‐driven synthesis of conductive polypyrrole was performed with a model cancer cell line. This was achieved in situ and could represent a new method of forming bioelectronic systems through a bottom‐up approach. We also present a new electrochemical method that sheds light on the mechanism of how cells instruct such polymerisation events.